2018
DOI: 10.3389/fimmu.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

A Recurrent Mutation in Anaplastic Lymphoma Kinase with Distinct Neoepitope Conformations

Abstract: The identification of recurrent human leukocyte antigen (HLA) neoepitopes driving T cell responses against tumors poses a significant bottleneck in the development of approaches for precision cancer therapeutics. Here, we employ a bioinformatics method, Prediction of T Cell Epitopes for Cancer Therapy, to analyze sequencing data from neuroblastoma patients and identify a recurrent anaplastic lymphoma kinase mutation (ALK R1275Q) that leads to two high affinity neoepitopes when expressed in complex with common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 84 publications
(110 reference statements)
3
26
0
Order By: Relevance
“…In addition to functional approaches, a bioinformatics approach called Prediction of T Cell Epitopes for Cancer Therapy (ProTECT) has been recently developed to identify ALK neoepitopes from recurrent ALK R1275Q mutation [37]. ProTECT allows the prediction of high affinity binders (epitopes) to common HLA alleles, with which a nonamer (AQDIYRASY) and two decamer sequences of ALK (MAQDIYRASY and AQDIYRASYY) with high affinities to HLA-B*15:01 were identified.…”
Section: Cytotoxic T-cell Responses Against Alk With Epitope Identifimentioning
confidence: 99%
“…In addition to functional approaches, a bioinformatics approach called Prediction of T Cell Epitopes for Cancer Therapy (ProTECT) has been recently developed to identify ALK neoepitopes from recurrent ALK R1275Q mutation [37]. ProTECT allows the prediction of high affinity binders (epitopes) to common HLA alleles, with which a nonamer (AQDIYRASY) and two decamer sequences of ALK (MAQDIYRASY and AQDIYRASYY) with high affinities to HLA-B*15:01 were identified.…”
Section: Cytotoxic T-cell Responses Against Alk With Epitope Identifimentioning
confidence: 99%
“…Each MHC-I heavy chain was expressed in E. coli, and refolded together with a high-affinity peptide and human β2m (hβ2m) (13,19). We utilized well-characterized epitopes: the p29 peptide (YPNVNIHNF) for H2-L d (41), the HIV gp120 P18-I10 peptide (RGPGRAFVTI) for H2-D d (42), the neuroblastoma related NRAS Q61K peptide (ILDTAGKEEY) for HLA-A*01:01 (43), and the HTLV-1 TAX peptide (LLFGYPVYV) for HLA-A*02:01 (44). Using a differential scanning fluorimetry assay (45), we further confirmed that all purified samples displayed thermal stabilities that were characteristic of properly conformed, peptide-bound molecular species with T m values ranging from 51 to 63 °C (Table S1).…”
Section: Tapbpr Recognizes Folded Pmhc-i Using a Conserved Binding Momentioning
confidence: 99%
“…Yet for a peptide bound to an MHC protein, the impact of features such as exposed hydrophobic surface and charges are determined by the peptide's conformation within the binding groove, as well as the size and position of the various amino acid side chains. Thus, efforts to predict peptide immunogenicity should be strengthened by approaches that account for the structural properties of peptide/MHC complexes (8, 16, 35).…”
Section: Introductionmentioning
confidence: 99%